Studi Komparatif Pengelolaan Anggaran Dana Desa - Rizka Yunika Ramly (Gorontalo Accounting Journal, 2019)
The purpose of this research to compare about the village fund budget management to reviewed from the Minister of Internal Affairs Regulation Number.113 of 2014. To comparing village fund budget management practice in Permata Village and Berlian village and than analyze the problems to occur in the practice of village fund management. Researchers want to provide a solution in the form of socialization of regulatory changed about village fund budget management to reviewed from the Minister of Internal Affairs Regulation Number.113 of 2014.The result of this research show the planing step, implementation, administration, and responsibiliy the village fund budget management in Permata village and Berlian village has been implemented according to regulations. But report pf Berlian village step still have a problem, The report was delayed, the report must be updateon the 10th of  the month.